Kebijakan Pemberdayaan Masyarakat : Melihat Kinerja Badan Pemberdayaan Perempuan, Masyarakat Dan Keluarga Berencana (BPPM - KB) Kota Pekanbaru Dalam Pelaksanaan Usaha Ekonomi Kelurahan - Eka Komalasari (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2020)
Women's Empowerment, Community and Family Planning Agency in the field of Community Economic Business Development is responsible for implementing the Village Economic Business Program, which is one of the empowerment programs that aims to improve the economy of the community. To develop the Kelurahan Economic Business program, the BPPM - KB is responsible for providing training, counseling and supervision of the implementers in each kelurahan. The problem is that not all kelurahan have succeeded in developing revolving funds and the number of bad loans so that the funds to be channeled back to the community are insufficient so that the community cannot borrow for their business. This is due to the lack of responsibility of the Women's Empowerment, Community and Family Planning Agency in the field of Community Economic Business development in carrying out their duties. This study aims to analyze the performance of women's and family-planning empowerment agencies in implementing community empowerment programs in the city of Pekanbaru (Study of Village Economic Enterprises). Data analysis was carried out qualitatively with data source triangulation techniques with stages of reduction, presentation and withdrawal and verification of data. The results showed that the performance of the Women's Empowerment Agency, Community and Family Planning was not maximal, training, counseling, direction and supervision activities were supposed to be carried out for all kelurahan but were not fulfilled, while the inhibiting factors of performance were the lack of employees who would go to each kelurahan in the city of Pekanbaru.